Online Payment Choice, Customer Trust and Accessibility of E-Commerce in Somalia - Jamal Yasin, Abdullahi; Ahmad, Abd Razak (Journal of Technology Management and Business, 2022)
Electronic payment refers to the use of electronic means of cash and related transactions, usually involving the use of computer networks such as the Internet and digital preserved value systems. Many countries in sub-Saharan Africa lack statistical information on the current state of the e-commerce market. Besides, a lack of trust in service providers also hinders the development of e-commerce. As such, this paper aims to examine e-commerce payment choice among e-commerce users and to determine the relationship between the factors to assess e-commerce payment and the accessibility of e-commerce in Somalia. The research method used is quantitative with a survey design. The questionnaire was distributed to 384 respondents, who are Hormuud Telecom subscribers residing in Somalia's capital, Mogadishu. The findings indicated that there is a positive relationship between online payment choice and accessibility of e-commerce, as well as a positive relationship between customer trust and accessibility of e-commerce. In conclusion, this study suggests that electronic payment can replace the paper payment method and customer trust plays an important role in e-commerce accessibility in Somalia.